If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + -5z = 15 Solving 25 + -5z = 15 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + -5z = 15 + -25 Combine like terms: 25 + -25 = 0 0 + -5z = 15 + -25 -5z = 15 + -25 Combine like terms: 15 + -25 = -10 -5z = -10 Divide each side by '-5'. z = 2 Simplifying z = 2
| e+4*2=14 | | 1/4(16f-4) | | x-23=k | | -2(7x-8)+5=14x+21 | | 80=4f+12 | | 4z/7-1=-7 | | -11=-5+3c | | 5=m/4-1 | | -4x-5y=-8 | | m=n+16 | | T=4s+3.67 | | 3j^2-26j+16=0 | | 2cos(3x)*cos(x)=-2 | | 3(1)-y=2(1)+y-1 | | x/8-7=9 | | 4xy-x^2+6x=0 | | 3x+2=8x+2 | | 8(t+2)=72 | | 6n^2-30n^2+24=0 | | (-55/6)=x-(x/2) | | 40=.25x | | 3z+2(4z-2)=5(3-2) | | 8x-7=2x+9 | | 3(2+2x)=18 | | 2(n+2)-8=24 | | 1/2(3a-1)=a-5 | | 4m-4/6m-20 | | 1/4(4t-9)=6 | | 5.5-8.1=-2.6 | | 4f^2-13f+9=0 | | -2(n+2)-8=24 | | .7x-2.9=.6 |